Avaliação clínica de três sistemas de remoção minimamente invasivos do tecido cariado - Saliba, Nemre Adas [UNESP]; Lima, Daniela Coêlho de [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; Okamoto, Ana Cláudia [UNESP] (My University, 2010)
The current philosophy of dentistry through the maximum preserving and minimum intervention has increased the interest in methods of ultraconservation cavities preparation. The aim of this study was to compare the ways of caries removal, mechanic and chemical-mechanic, using Carisolv™ and Papacárie® , in deciduous teeth evaluating the patients’ acceptability, presence and intensity of pain, anesthesia use, time of caries removal and presence of pain 24 hours after the treatments performance. The sample group was composed by 32 scholars between 6 and 10 years-old, mean age of 8.09 years and presenting as inclusion criteria at least two caries lesions in dentine. The children were divided in two groups of 16 patients. The Group I was represented by the mechanic and Carisolv™ treatments and the Group II, mechanic and Papacárie® . There was a great acceptability to the treatments (97%) and low anesthesia use (14%). In the Group I, 64% of the patients mentioned pain with the mechanical treatment and 33% of these classified it as strong. With Carisolv, 31% presented pain, and among them, 40% indicated it as strong. In the Group II, there was pain in 25% of children and of these, 50% identified it as strong, in both treatments. Only 6,25% of teeth treated showed a pain status 24 hours after the performance of the restorations. The mean time of the total caries removal by the mechanical and chemical-mechanical treatments in the Group I was respectively, in minutes, of 6.25 ± 2.33; 7.75 ± 2.49 and in the Group II of 6.75 ± 2.38; 7.37 ± 2.15. There were no differences statistically significant among the analyzed variables.

A atual filosofia da odontologia por meio da máxima preservação e mínima intervenção tem aumentado o interesse por métodos de preparos cavitários ultraconservadores. O objetivo do presente estudo foi comparar as formas de remoção de cárie, mecânica e químico-mecânica, utilizando Carisolv™ e Papacárie® , em dentes decíduos avaliando a aceitabilidade dos pacientes, presença e intensidade da dor, uso de anestesia, tempo de remoção do tecido cariado e presença de dor 24 horas após a realização dos tratamentos. O grupo amostral foi composto por 32 escolares, entre 6 e 10 anos, idade média de 8,09 anos e apresentando como critério de inclusão ao menos duas lesões de cárie de dentina. As crianças foram distribuídas em dois grupos contendo 16 participantes. O Grupo I foi composto pelos tratamentos mecânico e Carisolv™ e o Grupo II, mecânico e Papacárie® . Pôde-se observar uma grande aceitabilidade aos tratamentos (97%) e uma mínima utilização de anestesia (14%). No Grupo I, 64% dos pacientes relataram dor com o tratamento mecânico e destes, 33% a classificaram como forte. Com o Carisolv™ 31% apresentaram dor, sendo que destes 40% a indicaram como forte. No Grupo II, houve presença de dor em 25% das crianças sendo que destas, 50% a identificaram como forte, em ambos os tratamentos. Somente 6,25% dos dentes tratados apresentaram um quadro de dor 24 horas após a realização das restaurações. O tempo médio das remoções totais de cárie pelos tratamentos mecânicos e químico-mecânicos no Grupo I foi respectivamente, em minutos, de 6,25 ± 2,33; 7,75 ± 2,49 e no Grupo II de 6,75 ± 2,38; 7,37 ± 2,15. Dessa forma, não foram observadas diferenças estatisticamente significantes entre as variáveis analisadas.
Clinical evaluation of three systems minimally invasive removal of carious tissue
Keywords: Dental caries; Primary dentition; Pain; Anesthesia; Cárie dentária; Dentição decídua; Dor|Anestesia